American Housing Survey, 1994: MSA Core and Supplement File ([Verlag nicht ermittelbar], 1997)
This data collection provides information on characteristics of housing units in eight selected Metropolitan Statistical Areas (MSAs) of the United States. Data for each household member include age, sex, race, marital status, income, and relationship to the householder. For the householder, data also include tenure, length of residence, years of school completed, and Spanish origin. Variables pertaining to general housing characteristics cover number of rooms, type of heating and air-conditioning equipment, and whether the housing units had complete kitchens and plumbing facilities. Information on costs incurred for mortgage payments, rent, real estate taxes, property insurance, utilities, parking, and garbage collection permits comparisons of housing costs from one year to another between geographic areas. Limited data are provided on costs of additions, alterations, replacements, and repairs made to the property.